(untitled) (Bangladesh Medical Journal, 2025)
A thorough medical history, physical examination, and clinical presentation are crucial diagnostic processes for leukemia diagnosis. As a result, fatigue, irritability, and anorexia are common non-specific leukemia symptoms. Fever, pallor, lassitude, purpuric lesions, and bleeding are often the most common clinical observations and symptoms, which are usually indicators of the underlying thrombocytopenia, neutropenia, and anemia. This study aimed to evaluate the clinical presentation of leukemia in pediatric patients. This cross sectional study was conducted in the Department of Hemato-Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, for a period of 6 months from 1st September 2010 to 31st March 2011. A total of 80 diagnosed cases of leukemia among children aged 0 to 15 years who attended the study site were included in the study. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 15. The most prevalent (58.8%) age group among the 80 patients was ≤5 years, followed by 30.0% and 11.2% in age group of 5-10 and >10 years respectively. Regarding sex, the male to female ratio was 1.67:1, consisting of 62.5% males. The most frequent clinical symptom observed was fever, occurring in 95.0% of cases, followed by progressive pallor at 43.8%. Other notable clinical presentations included bone pain, lymph node enlargement, and haemorrhagic symptoms, with frequencies of 31.3%, 38.8%, and 25.0%, respectively. Additionally, headache (3.8%), vomiting (3.8%), abdominal distention (16.3%), a history of sore throat (1.3%), weight loss (2.5%), anorexia (3.8%), weakness (2.5%), and proptosis (1.3%) were also reported as presenting complaints. The presence of fever, which is then succeeded by increasing pallor, could be essential in the diagnostic procedures for leukemia. Bangladesh Med J. 2024 May; 53(2): 26-30